The Roles and Responsibilities of Notaries in Online Single Submission (OSS) Based Online Permits for Limited Liability Companies - Pamsukmayanti, Siska (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
A limited liability company business entity in carrying out its business activities requires a business license. In Indonesia, since 2018 business licensing has implemented online business licensing, namely the Online Single Submission System (OSS), which is a web-based application and is a business licensing issuing agency. contained in the AHU Online System is an important requirement. Where, the filling/registration in the AHU Online System is carried out by a Notary. This connection is the background of this research. The purpose of this research is to find out the roles and responsibilities of a notary in OSS business licensing for limited liability companies (PT) and to find out the obstacles and solutions in OSS business licensing for PT. The type of research used in this research is a juridical-empirical research type with a descriptive analytical nature. The data source used comes from primary data in the form of interview results and secondary data which includes primary legal materials and secondary legal materials. Data collection techniques were carried out using library research and interviews. Data analysis was carried out qualitatively by drawing deductive conclusions.Â The results of this study indicate that in business licensing OSS the notary acts as a general official making authentic deeds and an official who plays a role in registering limited company AHU Online data filling. Where, in carrying out its role, there is a risk of making mistakes which result in non-compliance with the rules so that the notarial deed becomes a private deed and the risk of errors in filling in the AHU data which results in failure in withdrawing the AHU data when submitting an application in the OSS system. The notary's responsibility for mistakes in making a deed that does not pay attention to the rules in making it and mistakes in filling in AHU data is a moral responsibility where the notary needs to be morally responsible for his actions by making improvements according to procedures and material responsibility where the notary bears the burden of costs incurred due to errors that occur. The limited liability company's obstacle in making applications to the OSS system is when there is a data discrepancy between the data in the OSS system and the data in AHU resulting in a failure in data retrieval. Apart from that, obstacles can also occur due to errors or incompatibility of dukcapil data or data on DGT Online.Abstract: Company; Online; Notary.